PENGGUNAAN MEDIA KARTU HURUF DALAM PENINGKATAN KEMAMPUAN MEMBACA AKSARA JAWA SISWA SEKOLAH DASAR - LESTARI, NOVIANA TRI (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract : The Using Card Letters Media in Improving Java Script Reading of Elementary School Students. The purpose of this research to improve Java script reading of elementary school students and to describe about steps of using card Javanese letters media improving Java script reading of elementary school students. This research is a collaborative classroom action research. This study was conducted in 2 cycles consisting of planning, action, observation, and reflection. Subjects were all students in the fourth grade school 1 Tamanwinangun academic year 2012/2013, amounting to 37 students. Data sources come from students, teacher, and observer. Data collection techniques are observation, interviews,questionnaire and tests. The validity of the source data using triangulation techniques and triangulation of data collection techniques. Analysis of data used role in action research is the analysis of quantitative data and qualitative data analysis. The conclusions of this research is the use of card letters media can improve of reading Javanese script of elementary school students and following steps: (a) letter cards held at chest height; (b) card revoked the letters one by one, (c) letter cards that have been removed are put in a certain place, and (d) the letter cards applied for various activities.. Keywords: card letters media, reading, Javanese script. Abstrak: Penggunaan Media Kartu Huruf dalam Peningkatan Kemampuan Membaca Aksara Jawa Siswa Sekolah Dasar. Tujuan penelitian ini adalah meningkatkan kemampuan membaca aksara Jawa melalui penggunaan media kartu huruf siswa sekolah dasar dan mendeskripsikan langkah-langkah yang tepat dalam menggunakan media kartu huruf yang dapat meningkatkan kemampuan membaca aksara Jawa siswa sekolah dasar. Penelitian ini merupakan penelitian tindakan kelas kolaboratif. Penelitian ini dilaksanakan dalam 2 siklus terdiri atas perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah seluruh siswa kelas IV SD Negeri 1 Tamanwinangun tahun ajaran 2012/2013 yang berjumlah 37 siswa. Sumber data yang digunakan adalah siswa, guru, dan observer. Teknik pengumpulan data dilakukan dengan observasi, wawancara, angket dan tes. Validitas data menggunakan teknik triangulasi sumber dan teknik triangulasi pengumpulan data. Analisis data yang dipergunakan dalan penelitian tindakan kelas ini adalah analisis data kuantitatif dan kualitatif. Simpulan penelitian ini adalah penggunaan media kartu huruf dapat meningkatkan kemampuan membaca aksara Jawa siswa sekolah dasar dan langkah-langkah penggunaan media kartu huruf sebagai beri-kut: (a) kartu huruf dipegang setinggi dada; (b) kartu huruf diambil satu persatu; (c) kartu huruf ditempel pada papan flanel; dan (d) kartu huruf digunakan untuk permainan. Kata Kunci: media kartu huruf, membaca, aksara Jawa.